THE TOP-IMPLART PROTON LINEAR ACCELERATOR: INTERIM CHARACTERISTICS OF THE 35 MEV BEAM. Issue 1 (29th May 2019) - De Angelis, C; Ampollini, A; Bazzano, G; Della Monaca, S; Ghio, F; Giuliani, F; Lucentini, M; Montereali, R M; Nenzi, P; Notaro, C; Placido, C; Piccinini, M; et al.
Abstract: In the framework of the Italian TOP-IMPLART project (Regione Lazio), ENEA-Frascati, ISS and IFO are developing and constructing the first proton linear accelerator based on an actively scanned beam for tumor radiotherapy with final energy of 150 MeV. An important feature of this accelerator is modularity: an exploitable beam can be delivered at any stage of its construction, which allows for immediate characterization and virtually continuous improvement of its performance. Currently, a sequence of 3 GHz accelerating modules combined with a commercial injector operating at 425 MHz delivers protons up to 35 MeV. Several dosimetry systems were used to obtain preliminary characteristics of the 35-MeV beam in terms of stability and homogeneity. Short-term stability and homogeneity better than 3% and 2.6%, respectively, were demonstrated; for stability an improvement with respect to the respective value obtained for the previous 27 MeV beam.